2021
DOI: 10.1016/j.pmedr.2021.101510
|View full text |Cite
|
Sign up to set email alerts
|

Self-rated health trajectories: A dynamic time warp analysis

Abstract: Self-rated health (SRH), individuals’ overall perception of their health, is a key predictor of health events. To target disease prevention efforts, it is important to understand how SRH develops over time. The goal of this short communication is to find prototypic SRH trajectories by applying dynamic time warping, a time series comparison technique initially developed for speech recognition. Revealing prototypic SRH trajectories can help direct disease prevention efforts towards trajectories that are more lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
2
2
0
Order By: Relevance
“…This explanation is also likely to hold for the association with unscaled total cost predicted risk, as SRH has been reported to remain fairly stable over time. 36 SRH has also previously been reported to be linked to frailty, as suggested by the findings of the present study. Both Pilleron et al 37 and Chu et al 38 have reported linkages between SRH and concomitant or subsequent frailty.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This explanation is also likely to hold for the association with unscaled total cost predicted risk, as SRH has been reported to remain fairly stable over time. 36 SRH has also previously been reported to be linked to frailty, as suggested by the findings of the present study. Both Pilleron et al 37 and Chu et al 38 have reported linkages between SRH and concomitant or subsequent frailty.…”
Section: Discussionsupporting
confidence: 88%
“…This is a likely explanation for the association with the ACG variable concurrent risk. This explanation is also likely to hold for the association with unscaled total cost predicted risk, as SRH has been reported to remain fairly stable over time 36. SRH has also previously been reported to be linked to frailty, as suggested by the findings of the present study.…”
Section: Discussionsupporting
confidence: 77%
“…Self-rated health, a construct that involves physical, mental and social aspects of life through the individual's general perception of his/her health [ 9 ], has been widely used in epidemiological studies because it is a simple, subjective, easy-to-evaluate and applicable measure [ 10 , 11 ]. It is also used for comparing health services and resource needs according to geographic areas and to calculate morbidity and mortality indicators [ 12 14 ] and functional decline [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The self-rated health, a construct that involves physical, mental and social aspects of life through the individual's general perception of their health [9], has been widely used in epidemiological studies, since it is a simple, subjective, easy-to-evaluate and applicable measure [10,11]. It is also used to compare health services, resource needs according to geographic areas, calculation of morbidity and mortality indicators [12][13][14] and functional decline [15,16].…”
mentioning
confidence: 99%